KERJASAMA INDONESIA BELANDA DALAM PENCEGAHAN PENYELUNDUPAN NARKOTIKA - Wicaksono, Mirza Agung; Susiatiningsih, Hermini; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research is explain the cooperation done by Indonesia and the Netherlands in the effort of preventing smuggling of narcotics and distribution to Indonesia by transnational crime syndicate. The research method used in this research is qualitative method, descriptive research type of analysis, and through library data collection techniques. Analysis of cooperation was also conducted to test the follow-up of cooperation between the two parties, namely Indonesia and the Netherlands. Cooperation in this research is analyzed by using achievement approach and interest which can be elaborated with the framework of thinking that is realism paradigm, concept of bilateral cooperation, and interest concept. The results of this analysis then prove that the cooperation between Indonesia and the Netherlands implemented in the relationship JCLEC - CILC - Interpol, is a less effective cooperation because there are still many interests between the two parties. This is because the absence of an Indoneisa-Dutch extradition treaty is due to prosecute the defend Narcotics Crimes who escaped to the Netherlands can not be done even though there has been communication to both parties up to Interpol.